(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
The study is concentrated with the role of inherent antioxidants content of selected mango varieties on the quality and shelf life of developed mango products. Three mango varieties as gutti, ashina, and langda and two mango products; mango bar and mango fruit drinks were used in this study. Antioxidant contents of three varieties of mango pulp and microbial loads of mango bar and mango fruit drinks were assessed. All three varieties contained vitamin A, beta carotene, and vitamin C as an antioxidant and their contents were higher in gutti variety than other two varieties; Asina and Langda. Antioxidants were made an effective role to resist microbial load in the mango products. No microbial growth was observed within three months in the products (mango bar and mango fruit drink) of gutti mango variety except total plate count (TPC), which showed slight growth after four months of storage. The other two products from Asina and Langda were affected by microbial growth as TPC within one and two months consecutively. The study discloses that the antioxidant content of mango varieties had significant effect on the quality and shelf life in mango products. Bangladesh J. Sci. Ind. Res. 52(4), 303-308, 2017